2010
DOI: 10.1038/nature09438
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of labelled endogenous β-actin mRNA during nucleocytoplasmic transport

Abstract: Export of mRNA occurs via nuclear pores, large nano-machines with diameters of roughly 120 nm that are the only link between nucleus and cytoplasm1. Hence, mRNA export occurs over distances smaller than the optical resolution of conventional light microscopes. There is extensive knowledge on the physical structure and composition of the NPC2–7, but transport selectivity and dynamics of mRNA export at nuclear pores remain unknown8. We developed a super-registration approach using fluorescence microscopy that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
307
7
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(352 citation statements)
references
References 31 publications
30
307
7
1
Order By: Relevance
“…68 Finally, the increased confinement within the pore may promote relatively fast transport via quasi one-dimensional diffusion. 67 All in all these scenarios are consistent with the notion that passage through the NPC is not a rate-limiting step 57 except when long-lived Kaps are depleted from the pore.…”
Section: Implications Of Kap-centric Controlsupporting
confidence: 73%
See 2 more Smart Citations
“…68 Finally, the increased confinement within the pore may promote relatively fast transport via quasi one-dimensional diffusion. 67 All in all these scenarios are consistent with the notion that passage through the NPC is not a rate-limiting step 57 except when long-lived Kaps are depleted from the pore.…”
Section: Implications Of Kap-centric Controlsupporting
confidence: 73%
“…40 Similar bimodal kinetics has also been reported for GFP-Kapb1 42 in permeabilized cells and mRNA export in living cells. 57 Interestingly, it was found that additions of exogenous Kapb1, 40 as well as other receptors 58 further reduced NPC permeability against passive cargoes, thereby recapitulating the role of Kaps as bona fide constituents of the NPC. Moreover, Yang and Musser, 36 as well as Timney et al 45 showed in vitro and in vivo respectively, that increasing amounts of Kaps expedited cargo import rates, rather than slowing it down.…”
Section: Cellular Evidence Of Kap-centric Controlmentioning
confidence: 97%
See 1 more Smart Citation
“…1C) (Shav-Tal et al 2004). Transcripts diffuse within the nucleoplasm for times ranging from 5 to 40 minutes; however, once a transcript engages a nuclear pore, export into the cytoplasm is fast (less than 0.2 sec) (Grunwald and Singer 2010;Mor et al 2010). Interestingly, transport through the nuclear pore takes only 5-20 min and docking on the nuclear side and release into the cytoplasm both take approximately 80 min, indicating that translocation through the nuclear pore is not the rate-limiting step (Grunwald and Singer 2010).…”
Section: Single Molecule Imaging Of Mrna In Gene Expressionmentioning
confidence: 99%
“…Before the work of Siebrasse et al (1), two studies of mRNA export in mammalian cells used mRNAs genetically engineered to contain a tandem array of fluorescent tags (10,11), together with a superregistration microscopy innovation in the latter (11). In contrast, Siebrasse et al…”
mentioning
confidence: 99%